The impact of the crusade ideas in Western Pomerania (from the twelfth to the first quarter of the thirteenth century) - Wasilkiewicz, Kamil (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2023)
The paper outlines the impact of the crusade ideas in Western Pomerania from the twelfth to the end of the first quarter of the thirteenth century, showing how it affected the region in three essential stages. The Western Pomeranians – attached to a traditional, native belief system – first encountered the crusade movement in the first half of the twelfth century, initially as its victims. Subsequently, the crusade ideas spread among the Western Pomeranian knights in the second half of the twelfth century as an element of the new, Christian culture. In the third stage, the region’s inhabitants became directly involved in the Fifth Crusade. In keeping with the historical methodology, the study is an attempt at a new, more comprehensive approach to the propagation of the crusade ideas in Western Pomerania and its effect on the locals. Also, the findings demonstrate that further research into the issue would be highly recommended.